In Vitro Test of Fraction N-Hexan, Aquadest and Crude Ethanol Extract of Moringa Leaves (Moringa oleifera L.) by Cholesterol Lowering Using a UV-Vis Spectrophotometer - Yusnita Usman; Muthmainna B (Jurnal Penelitian Pendidikan IPA, 2026)
This research is an experimental research study on in vitro test that uses sampling test from herbal medicine. The purpose of this study is to determine the anticholesterol activity and EC50 value of n-hexan farction, aquadest fraction and ethanol extract of moringa leaves. Moringa leaves (Moringa oleifera L.) contain secondary metabolite compounds that can lower blood cholesterol levels. The analysis method uses UV-Vis spectrophotometry at a wavelength of 665 nm with a series of test sample concentrations of 100 ppm; 300 ppm; and 500 ppm. Research data shows a decrease in cholesterol levels is directly proportional to the increase in concentration in the sample. The EC50 value of n-hexane partition was 142.57 ppm, aquadest partition was 737.88 ppm, and ethanol extract was 156,7 ppm. This indicates that the lower polarity of the solvent used in the extraction process, better than the anticholesterol activity of the extract. Conclusion, the best anticholesterol activity was found in the n-hexane fraction with an EC50 value of 142.57 ppm.